Training And Mentoring In Project-Based Learning For P5 Instruction For Mathematics Teachers At SMAN 2 Lumajang: Pelatihan Dan Pendampingan Project Based Learning Dalam Pembelajaran P5 Pada Guru Matematika Di SMAN 2 Lumajang - Alfiani Athma Putri Rosyadi; Yus M. Cholily; Baiduri; Zharla Zetira Aszahra; Galih Azhar Ramadhan; Jihan Nur Aini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The Merdeka Curriculum is a more flexible curriculum structure that focuses on essential material. This curriculum is not implemented simultaneously and massively, giving educational units the freedom to implement it. The Merdeka Curriculum provides references for teachers to develop independent teaching practices and share good practices. The problem is that not all schools receive this information equally. In its implementation, the Merdeka curriculum is associated with PjBL (Project Based Learning), a learning method that uses projects as a medium. In PjBL, students become the center of learning and conduct in-depth investigations into a topic. This community service was carried out at SMAN 2 Lumajang which had never been given assistance on PjBL in P5 (Pancasila Student Profile Strengthening Project).